Ensino religioso: um estudo comparativo entre duas escolas católicas no norte de Minas - Rodrigues, Janice Machado Ribeiro (2015)
Religion, much at the contrary to what many might think, raises rash debates in the global scientific community, given its importance for understanding human behavior, extending the boundaries of the Sciences of Religion (SR), as a scientific locus of Religious Education (RE), research object of this study, which has been analyzed in two private Catholic schools, to consider the influences of denomination and secularization in developing their teaching practices from the LDB 9.394 / 96, and if it is still able to influence the building up of their students religiosity. Both are traditional schools, which have contributed to the writing of the history, both educational and Catholic Christian, not only of the city itself but of the entire region of the north of Minas Gerais, as reference schools. In order to accomplish that, it has been necessary a scientific and epistemological approach to the subject, which has contributed to its mapping in the region, the county of Montes Claros / MG, where it is located the State University of Montes Claros, with undergraduate and graduate studies in SR, a relatively new subject area in the context of the courses offered. In order to address the problem which has motivated and structured this work, it have been developed historical reflections about the religious phenomenon, RE s object of study, as well as the influences that denomination and secularization have on it during the Brazilian society s development of modernization. The general purpose has been answered by the comparative analysis of empirical research data, that is, the questionnaires answered by the two institutions students enrolled in the last series of basic education and high school, where it has pointed out the importance of the RE and that it is still able to influence the students religiosity, even considering the existing influences of secularization, which has also been recognized by them. As for the hypotheses, they served to confirm that Catholic institutions suffer the influences of denomination, however, they are open to the modernity that has entered the school through the doors of the teaching practices which have been developed, but, above all, they seek to adequate the subject to the directions that have been established by the PCNs, state and federal guidelines and resolutions, changing it to the extent that it is found justification in the SR. Challenges still exist, because as a subject, the RE is established in the teaching field, which requires, in addition to methodologies, content and teachers able to develop it. The solution found in those schools was to seek in the SR, the theoretical foundation and the teachers specialized in the area, committed to the civic education of independent students